2019
DOI: 10.3390/microorganisms7020050
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic Analyses of Bradyrhizobium Reveal Uneven Distribution of the Lateral and Subpolar Flagellar Systems, Which Extends to Rhizobiales

Abstract: Dual flagellar systems have been described in several bacterial genera, but the extent of their prevalence has not been fully explored. Bradyrhizobium diazoefficiens USDA 110T possesses two flagellar systems, the subpolar and the lateral flagella. The lateral flagellum of Bradyrhizobium displays no obvious role, since its performance is explained by cooperation with the subpolar flagellum. In contrast, the lateral flagellum is the only type of flagella present in the related Rhizobiaceae family. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 63 publications
(100 reference statements)
1
12
0
6
Order By: Relevance
“…Notably, during the compilation of this paper, two phylogenomic analyses focusing on the genus Bradyrhizobium were published, but they did not include exactly the same taxa as our study. One study was also based on the core genome [50], whereas the other was based on the genome-to-genome blast distance phylogeny (GBDP) [51]. The phylogenetic trees of these two studies show a very similar topology to that presented here (), which confirms the robustness of these different phylogenomic analyses.…”
Section: Resultssupporting
confidence: 65%
“…Notably, during the compilation of this paper, two phylogenomic analyses focusing on the genus Bradyrhizobium were published, but they did not include exactly the same taxa as our study. One study was also based on the core genome [50], whereas the other was based on the genome-to-genome blast distance phylogeny (GBDP) [51]. The phylogenetic trees of these two studies show a very similar topology to that presented here (), which confirms the robustness of these different phylogenomic analyses.…”
Section: Resultssupporting
confidence: 65%
“…The alignment of FliL S and FliL L amino acid sequences indicated a low relationship, with 19.8% identity and 40% similarity between them ( Fig. S1B), in agreement with their pertaining to evolutionary different flagellar systems (3). To further characterize their relationship with other FliL proteins, we constructed the cladogram shown in Fig.…”
Section: Resultsmentioning
confidence: 52%
“…A recent study has identified orthologous flag-2 loci among members of the alpha-proteobacterial order Rhizobiales and furthermore, they are similar to the lateral flagellar system of Vibrio and Aeromonas spp. [15,37]. A more (See figure on previous page.)…”
Section: Discussionmentioning
confidence: 96%